Assessing tectonic and climatic controls for Late Quaternary fluvial terraces in Guide, Jianzha, and Xunhua Basins along the Yellow River on the northeastern Tibetan Plateau. (1st September 2018) - Guo, Xiaohua; Forman, Steven L.; Marin, Liliana; Li, Xiaolin
Abstract: This study focused on well-preserved fluvial terrace sequences that span the past 100 ka in the Guide, Jianzha, and Xunhua basins along the Yellow River that drained the northeastern Tibetan Plateau. New geomorphic, stratigraphic, sedimentologic and chronologic data from twelve depositional sequences within terraces yielded better constraints on rates of incision, degradational and aggradational phases for the Yellow River. Age control was established by sixteen OSL ages on quartz grains from fluvial sediments. Three fluvial aggradational phases were identified between 100 and 80 ka, 53 and 40 ka and 21 and 12 ka associated with terrace levels respectively at 120 to 95, 61 to 45 and 25 to 15 m above river level. These aggradational phases reflect multiple processes including enhanced fluvial discharge, sediment availability with glaciation, deglaciation and increased monsoonal precipitation. The initiation of fluvial degradation was linked to mega-floods released from landslide-dammed lakes at ca. 76, 38, and 16 ka, though these changes may also reflect variations in sediment-load discharge relations with climate change. The apparent net incision rate is 1.13 ± 0.11 mm/yr for the past 100 ka and is consistent with late Cenozoic tectonic uplift rates >0.5–2 mm/yr and recent GPS-based rates. The fluvial dynamics of the upper reach of the Yellow River was variably controlled by climate-induced changes in discharge sediment-load relations on stadial to interstadial timescales, episodic mega-floods from the breach of landslide dams, and with net incision in the past 100 ka in response to tectonic uplift of the Tibetan Plateau.